Integrating local users and multi-tiered institutions into the iwrm process - Lee, R., Herwehe, L. and Scott, C.A. (My University, 2015)
Participation among stakeholders and tiered institutions in a collaborative policymaking process is essential to IWRM&rsquos stated goals of securing water for people in a manner that reconciles economic efficiency, social equity, and environmental sustainability. Using the energy-water nexus and case examples from Tajikistan and Mexico, we define a mechanism by showing that poorly articulated multitiered institutional arrangements coupled with failure to generate truly participatory interaction of stakeholders lead to water insecurity. In the case examples, we found that the livelihoods of vulnerable populations are threatened when users experience water insecurity that is created or exacerbated when tiered institutions neglect users&rsquo signals by failure to respond with actions that promote sound resource management or mitigate livelihood threats. Water and livelihood security would be improved by adaptive actions targeted at user-defined causes of water insecurity and coordination between local resource users and institutions at multiple levels. Our results are a diagnostic tool that can be used to identify one cause that, among a possible multitude, contributes to water insecurity. Institutions and decision-making among stakeholders will be an explicit component of the human capacity to respond with programs, policies, and actions able to deal with the dual pressure on water resources posed by climate change and heightened demand while reconciling economic efficiency, social equity, and environmental sustainability. Institutions that operate at the intersection of local users and state and non-state actors have the greatest chance of inducing IWRM solutions if the tiered nature of linkages is expressly accounted for and used to adaptive advantage.
Keywords: IWRM, Multitiered institutions, Policy, Water-energy nexus, Water governance, Participatory approach